Development of a Master Sintering Curve for Al-Mg Alloy - Yong-Shin Lee; Sang-Jun Lee; Sangmok Lee; Eung-Zu Kim; Duck Jae Yoon (Advances in Materials Science and Engineering)
A new master sintering curve (MSC) is proposed for Al-Mg alloy in order to effectively design the pressure-assisted sintering process. In this work, hot pressing experiments of Al-Mg alloy powders are performed. The changes of relative density during hot pressing are measured for the various heating rates of 5°C/min, 10°C/min, and 20°C/min at the fixed pressure of 50 MPa. A work of sintering, designated as Θ, is introduced and defined as Θ(t,T)=∫0t1/Texp-Q/RTdt. A work of sintering, Θ, could be interpreted as a measure for the amount of sintering work. The MSC in this work defines the relation between the apparent density and a work of sintering, Θ. Since the measurement of an apparent activation energy, Q, is very difficult, the correct value of Q is obtained numerically using a mean residual square method. Then, the master sintering curves for sintering of Al-Mg alloy powders are proposed for the sintering temperatures of 400°C and 500°C through scaling procedures. It is expected that the master sintering curves proposed in this work could help an engineer to design pressure-assisted sintering process for Al-Mg alloy.